Curcumin‐embedded DBPC liposomes coated with chitosan layer as a fluorescence nanosensor for the selective detection of ribonucleic acid. (17th January 2022) - Estephan, Maria; El Kurdi, Riham; Patra, Digambara
Abstract: One of the limitations of fluorescence probe molecules during biomedical estimation is their lack of ability to selectively determine the targeted species. To overcome this there have been various approaches that involve attaching a functional group or aptamers to the fluorescence probe. However, encapsulating probe molecules in a matrix using nanotechnology can be a viable and easier method. Curcumin (Cur) as a fluorescence marker cannot distinguish DNA and RNA. This research reports a novel selective approach involving the use of nanocapsules composed of liposomal curcumin coated with chitosan for the selective detection of RNA molecules using a fluorescence method. The increase in RNA concentration enhanced the electrostatic interaction between the negatively charge surface of RNA and the positively charged nanocapsule, which was further verified by zeta potential measurement. This method had a low limit of detection (36 ng/ml) and higher linear dynamic ranges compared with other studies found in the literature. Moreover, the method was not affected by DNA and was selective for the detection of RNA molecules for which the site of interaction was confined only to uracil. The selectivity for RNA molecules towards other analogues species was also examined and recovery range found was between 99 and 100.33%. Abstract : Fluorescence nanosensor for the selective detection of ribonucleic acid using curcumin‐embedded DBPC liposomes coated with chitosan layer.